PENGARUH KARAKTERISTIK INDIVIDU, DAN MOTIVASIKERJA TERHADAP KINERJA KARYAWAN PADA PT. TELEKOMUNIKASI INDONESIA SEMARANG - NodariusLahagu, 13.05.51.0022 (Students Journal of Economic and Management, 2017)
This research takes object at PT. Telekomunikasi Indonesia Semarang. The problems raised in this study are, the influences of individual characteristics, and work motivation on employee performance at PT. Telekomunikasi Indonesia Semarang, in partially.The Population in this research are all of the employees at PT. Telekomunikasi Indonesia Semarang which amounted as many as 208 people. The sampling technique which used is random sampling with 66 respondents. The method of data analysis is quantitative method which consists of: test of validity, reliability, multiple regression analysis and hypothesis testing through t-test.The results showed that, individual characteristic variable has no effect on employee performance, and work motivation influenced on employee performance.